Emergency pancreatic surgery: demanding and dangerous - Strobel, Oliver; Schneider, Lutz; Philipp, Sebastian; Fritz, Stefan; Büchler, Markus W.; Hackert, Thilo (Langenbeck's archives of surgery, 2015)
Elective pancreatic surgery can be carried out with mortality rates below 5 % in specialized centers today. Only few data exist on pancreatic resections in emergency situations. The aim of the study was to characterize indications, procedures, and outcome of emergency pancreatic surgery in a tertiary center.
Gesehen am 24.06.2020